Another way to teach family: family nursing game (Acta Scientiarum. Health Sciences, 2014)
Current paper describes the application of an innovative strategy to teach family, within a hospital context, by sensitizing nurses on the family subject through the use of a game. Given the hospitalization of a relative, the family faces changes in its dynamics caused by the crisis it is exposed to. It is the relevance for including the family within the care process. Since nurses are expected to assume a key role for which they need specific competence to intervene in families when experiencing an eventual crisis. The in-service education becomes a strategy of generating new skills and enhances human capital to improve the quality of nursing care. Considering the importance of including family in the care context, a playful tool called Family Nursing Game has been invented for teaching the family, especially by passing a model of family intervention. The strategy is based on the belief of the existence of relationship between game and learning.